Study of an Accelerometer to Increase Energy Expenditure in Sedentary Individuals - Kapping, Anne; Swenson, Darrel; Algiers, A. J.; Ransom, Jessica (My University, 2010)
The Gruve accelerometer calculates daily energy expenditure and specifies a weekly energy expenditure goal that is specific to each individual. Using this information, we examined whether feedback from the Gruve accelerometer can positively influence people to increase their weekly energy expenditure in the form of non-exercise activity thermogenesis.
Color poster with text and graphs.
Keywords: Motivation (Psychology); Exercise--Psychological aspects; Energy metabolism--Measurement--Psychological aspects; Accelerometers--Psychological aspects; Posters